Compendium of contents essentials about water and sanitation - Briceño Araujo, Sarah Elisa (2024)
The Curricular Contextualization with a focus on Sustainability for Galapagos (CCSG) was issued on March 30, 2021 through Ministerial Agreement MINEDUC-MINEDUC-2021-00016-A, for the entire national educational system of the Galapagos Islands and is mandatory in all public, fiscomisional and private educational institutions of the province starting with the 2021-2022 school year. The Galapagos curriculum aligns the learning skills of the national curriculum with fourteen sustainability topics and issues for Galapagos, organized into transversal categories, on the general notions of: economy, environment and society, together with an articulation of the 17 Sustainable Development Goals (SDG) of the UN. The topic of Water and Sanitation is included in the curriculum as a subtopic within the Axis “Interdependence and Harmonious Coexistence in Nature” and the essential topic No. 7: “Water, Sanitation and Renewable Energy”. The implementation of the CCSG is carried out through collaborative work between teachers, students, allied external organizations and the Ministry of Education within the framework of a management model coordinated by the ECOS Foundation, through which teachers are provided with information, training and materials on each of the sustainability topics, which are supported and/or facilitated by local and international experts knowledgeable on the subject. For the topic of Water and Sanitation, technical assistance was provided by the Yachay Experimental Technology Research University (Yachay Tech University), the San Francisco University of Quito, the Un Cambio por la Vida Foundation and representatives of civil society, who together and after coordinated and arduous work developed the “Compendium of Essential Contents on Water and Sanitation”, which is a consultation document that systematizes the most relevant information on the topic and is aimed at teachers to design pedagogical activities for all sublevels of education. This resource is added to the other educational tools that have been developed on this important topic of the curriculum that has a great impact on the conservation and sustainable development of Galapagos.